Hedges as A Conversational Strategy in Women’s Gossip in The Bold Type Season 1 - Swasono, Endratno Pilih; Maisaroh, Hana (NOBEL: Journal of Literature and Language Teaching, 2023)
This study aims to explore the functions of hedges employed in women’s gossip by all female characters in The Bold Type Season 1. This study applied Coates’ (1996) classifications of hedges functions combined with two other functions proposed by Rabab’ah and Rumman (2015) to investigate the hedges function. The researchers employed a descriptive-qualitative method and collected the data by highlighting the transcript of the series to identify the conversations categorized as women’s gossip. The data were then analyzed in several steps; identifying by giving codes, classifying, interpreting or discussing, and making a conclusion. The study revealed that all four hedges’ functions by Coates and two functions by Rabab’ah and Rumman are found in female characters’ utterances in their gossip. Based on the study’s result, using hedges as a conversational strategy in female characters’ utterances smoothens their conversation during gossip. It can facilitate them to convey precise ideas when they exchange information and prevent them from delivering exaggerated information during gossip. It also helps them maintain solidarity and friendship between the participants, which is the overall function of female gossip. To conclude, hedges or hedging can be an influential conversational strategy in women’s gossip.